Echiniscus gemmatussp. nov. (Heterotardigrada: Echiniscidae; the spinulosus morphogroup) from Macau, China - Leong, Weng-I; Yu, Jr-Kai; Tsai, Isheng Jason; Kaczmarek, Łukasz; Lee, Yi-Chien; Lin, Chung-Ping (Zootaxa, 2024)
The study of tardigrades in urban environments, particularly in natural areas within cities, has been significantly overlooked. A recent discovery of a new species of tardigrade in lichens collected from Mong Há Hill Municipal Park in Macau provides new insights into the population of tardigrades within the city. Echiniscus gemmatus sp. nov. was identified based on distinct morphological characters, morphometric measurements, and DNA sequences of nuclear (18S rRNA, 28S rRNA, ITS-1, and ITS-2), as well as a mitochondrial (COI) markers. Our research indicates that Ech. gemmatus sp. nov. belongs to the Echiniscus spinulosus morphogroup and is most similar to Ech. tropicalis, as confirmed by both qualitative characters and DNA barcoding. Notably, Echiniscus gemmatus sp. nov. exhibits distinct characteristics that differentiate it from other members of the Ech. spinulosus morphogroup, including (1) often asymmetrical short spines B, C, Cd, Dd, and E, and (2) larger and more visible pores tend to be concentrated in the median and posterior portions of the first and second paired plates, with their visibility gradually decreasing towards the anterior and lateral suture regions.